Reshaping the Landscape: the Impact of COVID-19 on Social Science Research Methods and Practices - Agnihotri , Simmi; Singh , Vijay (International Journal of Applied and Scientific Research, 2024)
TThe COVID-19 pandemic has profoundly impacted the field of social science research, necessitating a re-evaluation of research methods and practices. This research explores the transformative efforts of COVID-19 on social science research, focusing on the changes in methodologies and practices that have emerged in response to the pandemic.Existing literature was reviewed on how the COVID-19 pandemic has affected research methods and practices in social sciences. Digital questionnaire was developed to collect primary data from social science researchers indicating the changes they have made in their research methods, the reasons behind these changes, and their perceptions of the effectiveness of these adaptations. Telephonic interviews and focused group discussions were conducted with the selected group of social scientists who have experienced significant changes in their research due to COVID-19. Their experiences, challenges, and innovative solutions they have employed have been explored. Secondary data was also generated from various online and offline platforms. Total 50 social science researchers were surveyed and interviewed. The results of the study shall be helpful to researchers, society, government and policymakers to pay special attention on this particular issue. The main findings and their implications for the field of social science research shall be summarized. The key ways in which the landscape has been reshaped by the COVID-19 pandemic shall be highlighted.